China saving's multiplier - Halvor Mehlum; Ragnar Torvik; Simone Valente (University of Oslo, Department of Economics, 2013)
China's growth is characterized by massive capital accumulation, made possible by high and increasing domestic savings. In this paper we develop a model with the aim of explaining why savings rates have been high and increasing, and we investigate the general equilibrium effects on capital accumulation and growth. We show that increased savings and capital accumulation stimulates further savings and capital accumulation, through an intergenerational distribution effect and an old-age requirement effect. We introduce what we term the savings multiplier, and we discuss why and how the one-child policy, and the dismantling of the cradle-to-grave social benefits provided through the state owned enterprises, have stimulated savings and capital accumulation.
Keywords: O11; D91; E21; 330; China; One-child policy; Overlapping generations; Growth; Savings